Screening microbial inoculants and their interventions for cross-kingdom management of wilt disease of solanaceous crops- a step toward sustainable agriculture - Kashyap, Abhijeet Shankar; Manzar, Nazia; Meshram, Shweta; Sharma, Pawan Kumar (Frontiers in Microbiology, 2023)
Microbial inoculants may be called magical bullets because they are small in size but have huge impact on plant life including humans. The screening of this beneficial microbes will give us an evergreen technology to manage harmful diseases of cross kingdom crops. The production is reducing as a result of multiple biotic factors and among them the bacterial wilt disease triggered by Ralstonia solanacearum is the most important in solanaceous crop. Examining the diversity of bioinoculants, results more microbial species having biocontrol activity against soil-borne pathogens. Reduced crop output, lower yields, and greater cost of cultivations are among the major issues caused by diseases in agriculture around the world. It is universally true that soil borne disease epidemics pose a greater threat to crop. These necessitate the use of ecofriendly microbial bioinoculants. This review article provides an overview of plant growth-promoting microorganisms bioinoculants their various characteristics, biochemical and molecular screening insights, modes of actions and interactions. The discussion is concluded with a brief overview of potential future possibilities for sustainable development of agriculture. This review will be useful for students and researchers to obtain an existing knowledge of microbial inoculants, their activities, and the mechanisms, which will facilitate the development of environmentally friendly management strategies for cross-kingdom plant diseases.